Ameliorative effects of Curcuma longa and Trigonella foenum graecum on liver lipid profile of alloxan-induced type-I diabetic rats - Shaik, Sadak Basha; Chennuru, Venkatakrishnaiah; Chappidi, Suryaprakash Reddy; Shaik, Sameena Fathima; Jamakala, Obaiah; Dornadula, Giri Raja Sekhar; Reddy, Manohar; Sadhu, Nelson Kumar; Abdul Rahman, Suzanah; Chilakala, Ramakrishna; Shaik, Mannur Ismail (Association for the Advancement of Zoology, 2023)
The aim of this study was to investigate the effects of Curcuma longa(CL),and Trigonella foenum graecum(TFG) in combination on protecting liver tissue from lipid peroxidation stress influenced by alloxan-induced diabetes, which is one of the most prevalent endocrine diseases globally,and exhibits a rapidly increasing growth rate among metabolic disorders. The study utilized eight groups of rats, each consisting of six individuals. Group I served as the control, followed by Groups II, III, and IV, which received treatments with CL, TFG, and CL + TFG, respectively. Type 1 diabetes was induced in rats through the intraperitoneal administration of alloxan at a single dose of 120mg/kg body weight. Group V served as the negative control (diabetic), and groups VI, VII, and VIII were diabetic rats treated with CL, TFG, and CL + TFG, respectively.The efficacy of CL and TFG extracts was determined based on lipid profiles(cholesterol, triglycerides, and phospholipids), and lipid peroxides (TBARS) in livertissue. After 30 days treatment with CL,and TFG, a significant reduction in the levels of lipid profile,and lipid peroxidation in liver tissue was observed compared to the Group V,which served as the diabetic control. The combinational approach of CL + TFG showed greater activity when compared to the individual treatment with plant extracts. Therefore, the combination of herbal treatment significantly mitigated the adverse effects caused by alterations in lipid profile in diabetic-induced rats.